Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024